2015
DOI: 10.1038/bjc.2015.337
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I expression impacts on patient survival and type and density of immune cells in biliary tract cancer

Abstract: Background:Biliary tract cancers (BTC) are rare malignant tumours with a poor prognosis. Previously, we have presented a detailed characterisation of the inflammatory infiltrate in BTC. Here, we analysed the impact of the expression of major histocompatibility complex class I (MHC I) on patient survival and the quantity, as well as the quality of tumour-infiltrating immune cell types in BTC.Methods:MHC I expression was assessed semi-quantitatively in 334 BTC, including extrahepatic (n=129) and intrahepatic cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 46 publications
2
53
0
1
Order By: Relevance
“…Furthermore, FoxP3 overexpression is accompanied by CTLA‐4 overexpression . Indeed, CTLA‐4 is expressed on the surface of Tregs and has to bind to CD80 on antigen‐presenting cells to exert inhibitory effects on cytotoxic cells . Interestingly, a deregulation of genes related to immune modulation in BTCs was more pronounced in the peritumoural than in the tumour tissue and facilitated tumour recurrence and chemo‐resistance.…”
Section: Mechanisms Of Immune Surveillance and Immune Escapementioning
confidence: 99%
“…Furthermore, FoxP3 overexpression is accompanied by CTLA‐4 overexpression . Indeed, CTLA‐4 is expressed on the surface of Tregs and has to bind to CD80 on antigen‐presenting cells to exert inhibitory effects on cytotoxic cells . Interestingly, a deregulation of genes related to immune modulation in BTCs was more pronounced in the peritumoural than in the tumour tissue and facilitated tumour recurrence and chemo‐resistance.…”
Section: Mechanisms Of Immune Surveillance and Immune Escapementioning
confidence: 99%
“…In comparison, intraepithelial tumor-infiltrating CD4+, CD8+, and Foxp3+ T lymphocytes, MHC I and NKG2D were referred as positive factors to prolong the overall survival of patients with BTC. The role of intraepithelial tumor-infiltrating CD8+ T lymphocytes, MHC I and NKG2D has been identified and reported a beneficial prognostic effect of high cell counts in a variety of human malignancies including BTC 8, 9, 11, 12, 27, 30-32. Goepport also found a better prognostic impact of both intraepithelial tumor-infiltrating CD4+ and Foxp3+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Studies identified immune cell types or ratio including CD4+, CD8+, and Foxp3+ Tumor-infiltrating T lymphocytes (TILs), IL17+, neutrophil recruitment (CD66b+), PD-1/CD8 TILs and neutrophil/lymphocyte (NLR), and analyzed the distribution and clinical relevance of these mediators 8, 10, 12-14. Others observed the impact of the expression of major histocompatibility complex class I (MHC I) and natural killer group 2 member D (NKG2D) 9, 11.…”
Section: Introductionmentioning
confidence: 99%
“…HCCs express low levels of MHC class I molecules in addition to costimulatory molecules [33] . Similarly, in BTC, Goeppert et al [34] analysed the impact of MHC expression on survival in a large series of patients ( n = 334) as well as the relationship of this to TIL. MHC I expression was assessed semi-quantitatively and divided into 2 groups of high and low expression.…”
Section: Immunogenicity Of Hepatobiliary Cancermentioning
confidence: 99%